COMPARISON OF LEGAL IN GRANTING THE RIGHTS OF RETITUTION TO VICTIMS OF SEXUAL VIOLENCE - Sari, Pika; Yanuarto, Toto; Setyawan, Effendi; Prakoso, Bhim (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The existence of an effective legal system for the protection and recovery of victims of sexual violence is important in the context of respect for justice. The problem is the legal protection of victims of sexual violence, and the granting of restitution rights to victims of sexual violence. This type of research includes a legal-normative section which examines theories, concepts, legal principles and legal provisions that are appropriate and relevant to the subject of the research. This research uses qualitative methods and case methods. In addition, the data obtained will be processed qualitatively and presented in descriptive form. In conclusion, legal protection for victims of sexual violence in Indonesia is regulated in Law Number 31 of 2014 concerning Protection of Witnesses and Victims. Victims of criminal acts have the right to receive compensation, compensation for loss of income or property. By providing the right to restitution to victims of sexual violence in Indonesia, it is clear that restitution or compensation recognizes the victim's suffering and provides adequate restitution. However, there are differences in policies regarding restitution for victims of sexual violence in Malaysia. Currently there is no law that clearly regulates this aspect. This condition can cause victims to feel insecure and have difficulty identifying their pain. Therefore, special attention must be paid to improving restitution rules to better guarantee the rights of victims of sexual violence.